The Applicable Law regulating contracting between absentees in electronic commerce contracts : " An Analytical study" - Sulaiman Dzay, Awaz (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
As a result of the increase in electronic commercial activity both internally and internationally and in line with the development in the field of information and communication technology and Internet activities, and to provide the legal foundations and frameworks for electronic transactions through modern means of communication, encouraging the Internet and information technology industry and its development, keeping pace with legal developments in electronic aspects and adapting the traditional legal system including In line with modern information and communication technology systems, the Iraqi legislator issued the Electronic Signature and Electronic Transactions Law No. (87) for the year 2012, which tried to regulate the issue of electronic contracts, but there is a problem that has been absent from the Iraqi legislator in terms of addressing it, which is the issue of determining the place of concluding the contract and thus solving the problem of determining The applicable law, neither did it specify the place of concluding the electronic commercial contract accurately to prevent falling into the problem of conflict of laws, nor did it refer explicitly to the text of Article 25/1 of the Iraqi Civil Code and thus this problem is solved, it was necessary for us to address the problem of the place of concluding the contract Determine the applicable law.